Optimization of Biochemical Treatment of Tannery Wastewater - K. IBRAHIM, NERAN; H. ALWAN, ALI; M. BARBOOTI, MAHMOOD (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The present work is concerned with the finding of the optimum conditions for biochemical wastewater treatment for a local tannery. The water samples were taken from outline areas (the wastewater of the chrome and vegetable tannery) in equal volumes and subjected to sedimentation, biological treatment, and chemical and natural sedimentation treatment.The Box-Wilson method of experimental design was adopted to find useful relationships between three operating variables that affect the treatment processes (temperature, aeration period and phosphate concentration) on the Biochemical Oxygen Demand (BOD5).The experimental data collected by this method were successfully fitted to a second order polynomial mathematical model. The most favorable operating conditions for the treatment are;Temperature 32.5oC,Aeration period 10 hours andphosphate concentration 16.8 mg/L.On using the optimum conditions a mathematical model simulating the operation for the treatment was obtained.